PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS V SD - Septriyani Gebi (Dharmas Education Journal (DE_Journal), 2021)
This type of research uses Classroom Action Research (CAR) which aims to portray the utilization of snakes and stepping stools media in further developing understudy learning results in friendly investigations subjects for 5th grade primary school, this exploration was led in two gatherings. Each gathering comprises of four phases, specifically, arranging, activity, perception, and reflection. The quantity of subjects was 19 individuals, comprising of 9 men and 10 ladies. The technique utilized as the principle strategy is perception and tests. The outcomes showed that through the snake and stepping stool game media there was an increment in friendly investigations understudy learning results. The outcomes showed that understudy learning results in friendly examinations subjects expanded using snakes and stepping stools game media. The normal worth of understudy learning results at the primary gathering was 53% while the subsequent gathering was 81.14%. The level of the amount of the two gatherings was 28.14%. From the consequences of these examinations, it very well may be inferred that there was an increase in the activities of students and teachers as well as student learning outcomes after the application of the snake and ladder game media in social studies subjects.